2005
DOI: 10.1038/sj.bdj.4812928
|View full text |Cite
|
Sign up to set email alerts
|

British Dental Journal based Continuing Professional Development: A survey of participating dentists and their views

Abstract: Objective There is little information available on journal based verifiable continuing professional development (CPD). The aim of this study was to survey those dentists who have undertaken this form of CPD and elicit their views. Design A questionnaire survey. Method Four hundred dentists who had registered to undertake CPD with the British Dental Journal (BDJ) were randomly selected and sent a questionnaire. Results Three hundred and twelve questionnaires were returned (78%) of these 181 (58%) were male and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 4 publications
2
14
0
Order By: Relevance
“…This is in accordance with a previous study by Absi et al (2011) who identified that there was a considerable improvement in the knowledge of the participants (75%) immediately after attending a course, although a loss in knowledge was observed between 6 and 12 months following the course . Moreover, a previous study of dentists found that 92.2% of the participants agreed/strongly agreed with knowledge increase after CE initiative . A recent study also reported similar findings of knowledge gain through CE programme on leadership …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is in accordance with a previous study by Absi et al (2011) who identified that there was a considerable improvement in the knowledge of the participants (75%) immediately after attending a course, although a loss in knowledge was observed between 6 and 12 months following the course . Moreover, a previous study of dentists found that 92.2% of the participants agreed/strongly agreed with knowledge increase after CE initiative . A recent study also reported similar findings of knowledge gain through CE programme on leadership …”
Section: Discussionsupporting
confidence: 91%
“…An improvement in dental practice was reported by 53.7% of the participants in our study. Even higher proportions of the dentists (72%‐73%) in two previous studies in the UK rated the impact of attending a course on dental practice as great or very great . Similarly, a study of dentists in Australia identified an improvement in technical knowledge, increased adoption of new technologies, positive impact on dental practice and improved healthcare outcomes with CE programmes .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[16][17][18][19][20] These are expected results and it links in with the literature where students chose dentistry as a profession due to its positive image. [21][22][23] Complying with the GDC standards and regulations together with continuous professional development 24,25 are the main focus of dental practitioners and therefore it is not surprising that when it comes to the term 'dental law', words like 'regulations' and 'standards' were on the top of the list of the selected choices. This paper highlights the relevance and the links of the regulations for this group of students in their perception about dental law.…”
Section: Discussionmentioning
confidence: 99%
“…Along with attending postgraduate courses and discussion with colleagues, reading journals is one of the most frequent forms of CPD undertaken by dentists (Bullock et al, 2003;Buck and Newton, 2002). Journalbased CPD has been reported to be an effective way of undertaking verifiable CPD (Tredwin et al, 2005). We are currently beginning the process of improving CPD provided by the Journal of Orthodontics.…”
mentioning
confidence: 99%